Are Australian junior doctors failing to act as health advocates? A qualitative analysis. (9th June 2022) - Maloney, Daniel P.D.; Moodie, Rob; Daube, Mike; Wilson, Alyce N.
Abstract: Objective : To explore junior doctors' attitudes towards and experiences of health advocacy practice and teaching in Australia. Methods : Semi‐structured interviews were conducted with 15 junior doctors across Australia. Data were thematically analysed. Results : Three themes were identified: i) participants inconsistently understood and practised health advocacy, with many failing to conduct any advocacy work; ii) distinct factors motivated and enabled participants to undertake health advocacy; however, these were largely unrelated to any formal medical education; iii) the current medical workplace and education system is non‐conducive to health advocacy practice given the numerous barriers faced by junior doctors when engaging with health advocacy. Conclusions : Health advocacy is generally poorly taught, weakly understood, and rarely performed despite being one of the four core graduate competencies of the Australian Medical Council (AMC). The AMC must clearly define health advocacy and its scope in their outcome statements, and this must be translated into medical education curricula and advocacy opportunities in the workplace. Implications for public health : Doctors are well‐placed to act as public health advocates, yet they are denied the encouragement and training to do so. With the growing burden of complex and sensitive public health issues, junior doctors should be trained and encouraged in health advocacy.